Graphene oxide quantum dots attached on wood-derived nanocellulose to fabricate a highly sensitive humidity sensor. (15th July 2022) - Huang, Lijun; Yang, Yutong; Ti, Pu; Su, Guoting; Yuan, Quanping
Abstract: Herein, cellulose nanofibril (CNF) with various carboxyl amounts were prepared via regulating its oxidation degree using TEMPO oxidation. The CNF dispersion was dropped onto the interdigital electrode to be capacitive humidity sensor by the subsequent vacuum freeze-drying. Pure CNF-7 (NaClO content of 7 mmol/g) humidity sensor involves in orderly porous structure, which displays better performance than other CNFs for its moderate carboxyl content and dimension. As uniformly adding appropriate content of graphene oxide quantum dots (GOQD) with larger surface area and active sites, it can be attached on the CNF to construct a three-dimensional interconnected porous structure for their excellent aqueous dispersity as well as differences in morphology and size. Consequently, the CNF/GOQD sensor exhibits the sensitivity as high as 51, 840.91 pF/% RH, short response time (30 s)/recovery time (11 s) and excellent reproducibility. The proposed method can provide effective guidance for the design of humidity sensors based on nanomaterials. Graphical abstract: Unlabelled Image